2022
DOI: 10.3389/frsus.2022.902071
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Exergy, Entropy Generation Minimization, and Exergoenvironmental Analyses of Energy Systems-A Mini-Review

Abstract: Meeting the growing energy demands has become a crucial challenge, which should employ energy integration and benefit from the extraction of the maximum thermodynamic potential of the resources consumed. This brief review presents an overview of the essential elements of the methods of energy, exergy, entropy generation minimization, and exergoenvironmental analyses. In combination, these methodologies constitute a powerful toolbox for the design, analysis, and optimization of energy systems. The quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Exploiting the ability to quantify the degree of irreversibility by means of the entropy generation, which can be considered as a function that depends on the path followed by the thermodynamic process and on geometrical parameters of the system design, made it possible to use the Entropy Generation Analysis along with the Entropy Generation Minimization (EGM) [ 8 , 143 ]; see also [ 31 ] for optimization purposes.…”
Section: Ega As An Optimization Toolmentioning
confidence: 99%
See 4 more Smart Citations
“…Exploiting the ability to quantify the degree of irreversibility by means of the entropy generation, which can be considered as a function that depends on the path followed by the thermodynamic process and on geometrical parameters of the system design, made it possible to use the Entropy Generation Analysis along with the Entropy Generation Minimization (EGM) [ 8 , 143 ]; see also [ 31 ] for optimization purposes.…”
Section: Ega As An Optimization Toolmentioning
confidence: 99%
“…Bejan [ 8 ] was the first to provide a review of the development and adoption of the Entropy generation minimization (finite time thermodynamics, or thermodynamic optimization) in several sectors of relevant practical importance, such as cryogenics, heat transfer, education, storage systems, solar power plants, nuclear and fossil power plants, as well as refrigerators. Ordonez et al [ 143 ] reported, in their recent review on the thermodynamic methods of analysis, the concepts of the exergy and entropy generation in order to assess system performance by means of metrics that quantify the degrees of irreversibility.…”
Section: Ega As An Optimization Toolmentioning
confidence: 99%
See 3 more Smart Citations